Trans-Cultural Validation of the “Academic Flow Scale” (Flow 4D 16) in Arabic Language: Insights for Occupational and Educational Psychology From an Exploratory Study - Chalghaf, Nasr; Azaiez, Chiraz; Krakdiya, Hela; Guelmami, Noomen; Re, Tania Simona; Maldonado Briegas, Juan José; Zerbetto, Riccardo; Del Puente, Giovanni; Garbarino, Sergio; Bragazzi, Nicola Luigi; Azaiez, Fairouz (Frontiers in Psychology, 2019)
Background: As an optimal psychological state, flow represents those moments when everything comes together for the performer. Flow is often associated with high levels of performance and is a positive psychological experience. Aims: Our study aimed to validate the academic flow scale (Flow 4D 16) in Arabic language across Tunisian population, and to test its factor structure, in terms of internal consistency/reliability, predictive validity, and sensitivity. Method: The population is composed of 320 students (139 men and 181 women) belonging to the University of Sfax, with a mean age of 22.26 years. The students voluntarily responded to the scale of academic flow (Flow 4D 16). Both exploratory (EFA) and confirmatory (CFA) factor analyses were performed. Results: The four-dimensional alpha coefficients of the Flow 4D 16 indicate an excellent internal consistency, respectively of .902 (Cognitive), .959 (time), .974 (Ego) and .960 (Well-being). The CFA fit indices were satisfactory. Conclusion: In summary, the 16-items model (original version) showed for all the indices an excellent fit to the theoretical model, confirming the four-dimensional factor structure among Tunisian student population